Silver-ruthenium alloy slurry suitable for multilayer ceramic capacitor and preparation process of silver-ruthenium alloy slurry

The preparation of silver ruthenium alloy powder by laser method and combined with ball milling stirring process, the problem of oxygen absorption expansion and reduction and degassing of silver palladium alloy during sintering is solved, and high-quality silver ruthenium alloy paste is achieved, meeting the technical requirements of multi-layer ceramic capacitors.

CN119560309AInactive Publication Date: 2025-03-04NORTHEASTERN UNIV CHINA
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411734246.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The silver-palladium alloy, the internal electrode material of the existing multi-layer ceramic capacitor, is prone to oxygen absorption expansion and reduction and deflation during the sintering process, resulting in a decrease in the mass of the sintered film and a delamination of silver-rich and palladium-rich phases.

Method used

The silver ruthenium alloy powder was quickly prepared by laser method, and a silver ruthenium alloy paste with good alloy degree, uniform particle size distribution and dispersion were prepared through reasonable raw material ratio and ball milling stirring process.

Benefits of technology

The efficient preparation of silver-ruthenium alloy materials is achieved, which avoids the problems of silver migration and expansion and deflation at high temperatures, improves the quality and continuity of the sintered film, and meets the technical requirements of multi-layer ceramic capacitors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005161069500000011
    Figure HDA0005161069500000011
  • Figure HDA0005161069500000012
    Figure HDA0005161069500000012
Patent Text Reader

Abstract

The invention relates to a silver-ruthenium alloy slurry suitable for a multilayer ceramic capacitor and a preparation process thereof, and the preparation process comprises the following specific steps: carrying out sandpaper polishing pretreatment on a ruthenium target to remove a surface oxide layer, and drying to obtain a treated ruthenium target; the treated ruthenium target is immersed in a solution containing silver nitrate, and nanosecond pulse laser is focused on the surface of the ruthenium target for laser scanning ablation; and after ablation is completed, the ruthenium target is taken out, liquid obtained after laser scanning ablation is collected, centrifugal collection is carried out, drying treatment is carried out after cleaning and centrifuging, and a powder product, namely the silver-ruthenium alloy material is obtained. And putting the obtained silver-ruthenium alloy material, an organic auxiliary agent, inorganic nonmetal powder and other metal powder into a ball mill according to a proportion, uniformly mixing under high-energy grading ball milling and stirring, and keeping the temperature for a period of time to obtain the silver-ruthenium alloy slurry. The silver-ruthenium alloy slurry has the advantages of high-temperature sintering resistance, simple preparation process, narrow particle size distribution, controllable particle size, good dispersity and stability and the like, and overcomes the defects of poor stability, no high-temperature resistance, complex preparation process and the like of the existing conductive slurry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of conductive pastes, and in particular to a silver-ruthenium alloy paste suitable for multilayer ceramic capacitors and a preparation process thereof. Background Art

[0002] Multilayer ceramic capacitors (MLCC) have excellent characteristics such as wide capacity range, good frequency characteristics, ultra-small size, and non-polarity, and are widely used in military and aviation fields. Due to the rapid development of the global electronics industry, MLCC will usher in a peak period of development, increasing at a rate of 10% to 15% per year. The manufacturing process of MLCC is to co-fire the internal electrode and ceramic material into an integral structure. The production of internal electrodes can only choose precious metal (PME) materials with high melting point, low resistivity, and not easy to oxidize. Traditional MLCC internal electrode materials mostly use silver-palladium alloy or pure palladium. Silver-palladium slurry is widely used as electrodes in chip resistors, MLCC capacitors, chip inductors and other external components due to its excellent sintering resistance, weldability, anti-migration ability and moderate price. Silver-palladium alloy powder, as the key raw material of silver-palladium slurry, overcomes the shortcomings of silver's inability to withstand burning and silver migration at high temperatures. However, the alloy preparation process is prone to oxygen absorption expansion and reduction and degassing, resulting in a decrease in the quality of the sintered film and the easy formation of stratification of silver-rich phases and palladium-rich phases. Therefore, there is an urgent need in the art to provide an antioxidant conductive alloy powder having good alloying degree, narrow particle size distribution and excellent dispersity and a preparation process thereof.

[0003] Silver-ruthenium alloy has high density, hardness, melting point and high temperature stability, as well as good electrical and thermal conductivity. It is an alloy material with multiple excellent properties and wide application value. Silver-ruthenium alloy is difficult to synthesize economically and efficiently due to its complex preparation process and long process. In order to meet the needs of multilayer ceramic capacitors for high-performance conductive paste, it is necessary to develop a silver-ruthenium alloy paste and its preparation process that can be quickly prepared for multilayer ceramic capacitors. Summary of the invention

[0004] According to the above-mentioned technical problems of poor alloy degree, uneven particle size distribution, difficult metal alloying preparation, and long process flow, the present invention provides a silver-ruthenium alloy slurry with good alloy degree, particle size distribution and dispersibility, and a simple process flow and its preparation process. The present invention mainly uses a laser method to quickly prepare silver-ruthenium alloy powder through an innovative preparation process, and then improves the preparation of conductive slurry through a reasonable raw material ratio, so that its performance, alloy degree, dispersibility and morphology are all suitable for the technical requirements of MLCC slurry production.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows: a silver-ruthenium alloy slurry suitable for multilayer ceramic capacitors and a preparation process thereof, characterized in that the preparation method of the slurry comprises the following steps:

[0006] S1. The ruthenium target is pre-treated by sandpaper polishing to remove the oxide layer on its surface, and a treated ruthenium target is obtained after drying; the treated ruthenium target is immersed in a solution containing silver nitrate, and a nanosecond pulse laser is used to focus on the surface of the ruthenium target for laser scanning and ablation; after the ablation is completed, the ruthenium target is taken out, and the liquid after the laser scanning and ablation is collected and centrifuged, and after washing and centrifugation, it is dried to obtain a powder product, which is a silver-ruthenium alloy material.

[0007] S2. The silver-ruthenium alloy material obtained in step S1 is placed in a ball mill with an organic additive, an inorganic non-metallic powder, and other metal powders in proportion and mixed evenly under high-energy graded ball mill stirring. After keeping warm for a period of time, a silver-ruthenium alloy slurry is obtained.

[0008] The purity of the ruthenium target in step S1 is greater than 99%.

[0009] The silver nitrate-containing solution in step S1 comprises 0.1 to 2.5 mol / L of silver nitrate and 0.1 to 10 g / L of a surfactant, polyvinyl pyrrolidone (PVP).

[0010] The parameters of the nanosecond pulse laser described in step S1 are: laser energy of 1 to 50 W, and wavelength of 266 nm to 10.6 μm.

[0011] The laser scanning ablation described in step S1 is performed for 0.1 to 3 hours, and the particle size of the silver-ruthenium alloy material is controlled to be 10 nm to 2 μm.

[0012] The weight proportions of the components of the silver-ruthenium alloy slurry described in step S2 are: 50-90% of silver-ruthenium alloy material, 2-20% of organic additives, 2-15% of inorganic non-metallic powder, and 6-15% of other metal powders.

[0013] The organic auxiliary agent described in step S2 includes one or more of terpineol, butyl carbitol, oleic acid, stearic acid, ethyl acetoacetate, butyrylacetone, polyethylene glycol, epoxy resin, polydimethylsiloxane, ethyl cellulose, amino acid, hexadecyltrimethylammonium bromide, mercaptan, sodium dodecylbenzene sulfonate, and sodium polyacrylate.

[0014] The inorganic non-metallic powder described in step S2 is one or more of silicon oxide, cerium oxide, carbon powder, aluminum oxide, zinc oxide, titanium carbide, and titanium diboride.

[0015] The other metal powders described in step S2 are one or two of pure silver powder, ruthenium powder, palladium powder, copper powder or nickel powder with a particle size ranging from 20 nm to 2 μm.

[0016] The stirring conditions of the high-energy graded ball milling described in step S2 are as follows: a ball milling speed of 500 to 2000 rpm, a ball milling time of 0.5 to 5 h, a ball graded diameter range of 0.5 to 5 cm; and a holding temperature of 20 to 90° C. after ball milling for 0.5 to 2.5 h.

[0017] Compared with the conventional liquid phase method for preparing pure silver or silver-palladium alloy slurry, the present invention has the following advantages:

[0018] 1. The silver-ruthenium alloy material obtained by the present invention has a good alloy state, a morphology closer to a sphere, and a uniform particle size distribution, which well meets the technical requirements of the silver-palladium paste.

[0019] 2. The silver-ruthenium alloy used in the present invention has a simple preparation process, a narrow particle size distribution, and a controllable particle size. By adjusting and controlling, a silver-ruthenium alloy in the range of 20 nm to 2 μm can be accurately obtained.

[0020] 3. The silver-ruthenium alloy obtained by the present invention is resistant to high-temperature oxidation and will not cause defects such as silver migration and expansion and degassing at high temperatures.

[0021] 4. The silver-ruthenium alloy preparation process adopted in the present invention does not involve a large amount of solvents and complex solution reduction, has a short process flow, and is green and environmentally friendly.

[0022] 5. The silver-ruthenium alloy slurry obtained by the present invention has good dispersibility, is not prone to sedimentation, does not crack during sintering, and has viscosity and thixotropy that can meet the requirements for printing use. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the technical solution of the product of the present invention, the following is a brief introduction to the drawings of the present invention. The drawings and the following specific embodiments are used to explain the present invention, but do not constitute a limitation of the present invention.

[0024] Figure 1 Scanning electron microscope image of the silver-ruthenium alloy material of Example 1.

[0025] Figure 2 XRD spectrum of the silver-ruthenium alloy material of Example 1. DETAILED DESCRIPTION

[0026] The present invention is further described in detail below in conjunction with the embodiments, but the protection scope of the present invention is not limited thereto.

[0027] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0028] Example 1

[0029] A ruthenium target with a purity of 99.1% is pre-treated by sandpaper polishing to remove its surface oxide layer, and a treated ruthenium target is obtained after drying; the treated ruthenium target is immersed in a solution containing 0.1 mol / L silver nitrate and 0.1 g / L PVP, and a nanosecond pulse laser is used to focus on the surface of the ruthenium target for laser scanning ablation, and the laser energy is controlled to be 1 W, the wavelength is 266 nm, and the laser scanning ablation time is controlled to be 3 hours, so as to obtain a silver-ruthenium alloy material with a particle size of about 0.5 μm. After the ablation is completed, the ruthenium target is taken out, the liquid after the laser scanning ablation is collected and centrifuged, and after washing and centrifugation, it is dried to obtain a powder product, that is, a silver-ruthenium alloy material.

[0030] The obtained silver-ruthenium alloy material, organic additive (pinene alcohol, epoxy resin and amino acid are mixed in a mass ratio of 1:1:1), silicon oxide, and silver powder in a mass ratio of 50%:20%:15%:15% are placed in a ball mill and mixed evenly under high-energy graded ball mill stirring. The high-energy graded ball mill stirring conditions are controlled to be a ball mill speed of 500rpm, a ball mill time of 0.5h, and a bead diameter of 0.5cm and 5cm graded in a ratio of 1:1. After ball milling, the silver-ruthenium alloy slurry is obtained by keeping the temperature at 20°C for 2.5h.

[0031] Example 2

[0032] A ruthenium target with a purity of 99.5% is pre-treated by sandpaper polishing to remove its surface oxide layer, and a treated ruthenium target is obtained after drying; the treated ruthenium target is immersed in a solution containing 2.5 mol / L silver nitrate and 10 g / L PVP, and a nanosecond pulse laser is used to focus on the surface of the ruthenium target for laser scanning ablation, and the laser energy is controlled to be 50 W, the wavelength is 10.6 μm, and the laser scanning ablation time is controlled to be 0.1 hours, so as to obtain a silver-ruthenium alloy material with a particle size of about 15 nm. After the ablation is completed, the ruthenium target is taken out, the liquid after the laser scanning ablation is collected and centrifuged, and after washing and centrifugation, it is dried to obtain a powder product, that is, a silver-ruthenium alloy material.

[0033] The obtained silver-ruthenium alloy material, stearic acid, inorganic non-metallic powder (zinc oxide, titanium carbide, titanium diboride mixed at a mass ratio of 1:0.5:0.5), and other metal powders (nickel powder and copper powder mixed at a mass ratio of 1:5) were placed in a ball mill at a mass ratio of 90%:2%:2%:6% and mixed evenly under high-energy graded ball milling stirring. The high-energy graded ball milling stirring conditions were controlled to be a ball milling speed of 2000rpm, a ball milling time of 5h, and a bead diameter of 0.6cm, 0.9cm and 2cm graded at a ratio of 1:1:1. After ball milling, the silver-ruthenium alloy slurry was obtained by keeping the temperature at 90°C for 0.5h.

[0034] Example 3

[0035] A ruthenium target with a purity of 99.9% is pre-treated by sandpaper polishing to remove its surface oxide layer, and a treated ruthenium target is obtained after drying; the treated ruthenium target is immersed in a solution containing 1.5 mol / L silver nitrate and 5 g / L PVP, and a nanosecond pulse laser is used to focus on the surface of the ruthenium target for laser scanning ablation, and the laser energy is controlled to be 34 W, the wavelength is 532 nm, and the laser scanning ablation time is controlled to be 1.5 hours, so as to obtain a silver-ruthenium alloy material with a particle size of about 100 nm. After the ablation is completed, the ruthenium target is taken out, the liquid after the laser scanning ablation is collected and centrifuged, and after washing and centrifugation, it is dried to obtain a powder product, that is, a silver-ruthenium alloy material.

[0036] The obtained silver-ruthenium alloy material, organic additive (butyl carbitol and polyethylene glycol are mixed in a mass ratio of 1:2), inorganic non-metallic powder (cerium oxide and carbon powder are mixed in a mass ratio of 1:0.1), and other metal powders (ruthenium powder and palladium powder are mixed in a mass ratio of 1:0.5) are placed in a ball mill in a mass ratio of 75%:10%:5%:10% and mixed evenly under high-energy graded ball milling stirring. The high-energy graded ball milling stirring conditions are controlled to be a ball milling speed of 1200rpm, a ball milling time of 3.5h, and a bead diameter of 0.9cm, 1.2cm and 3.5cm in a ratio of 1:0.5:1.5. After ball milling, the silver-ruthenium alloy slurry is obtained by keeping the temperature at 75°C for 1.2h.

[0037] Example 4

[0038] A ruthenium target with a purity of 99.25% is pre-treated by sandpaper polishing to remove its surface oxide layer, and a treated ruthenium target is obtained after drying; the treated ruthenium target is immersed in a solution containing 1.58 mol / L silver nitrate and 3.5 g / L PVP, and a nanosecond pulse laser is used to focus on the surface of the ruthenium target for laser scanning ablation, and the laser energy is controlled to be 29 W, the wavelength is 1064 nm, and the laser scanning ablation time is controlled to be 2.3 hours, so as to obtain a silver-ruthenium alloy material with a particle size of about 1.8 μm. After the ablation is completed, the ruthenium target is taken out, the liquid after the laser scanning ablation is collected and centrifuged, and after washing and centrifugation, it is dried to obtain a powder product, that is, a silver-ruthenium alloy material.

[0039] The obtained silver-ruthenium alloy material, organic additive (ethyl acetoacetate, butyrylacetone and polydimethylsiloxane are mixed in a mass ratio of 1:0.5:1.5), aluminum oxide, and palladium powder are placed in a ball mill in a mass ratio of 63%:7%:15%:15% and mixed evenly under high-energy graded ball mill stirring. The high-energy graded ball mill stirring conditions are controlled to be a ball mill speed of 950rpm, a ball mill time of 2.2h, and a bead diameter of 0.7cm, 0.8cm and 0.9cm in a ratio of 1:0.5:0.5. After ball milling, the silver-ruthenium alloy slurry is obtained by keeping the temperature at 42°C for 1.3h.

[0040] The silver-ruthenium alloy slurry prepared above was used to prepare a multi-layer ceramic capacitor by screen printing, and the sintering temperature was 950-1350°C. Using traditional commercial silver-palladium alloy slurry for comparison, the square resistance of the film layers obtained in Examples 1 to 4 was reduced by 20%, 15%, 26%, and 17% respectively compared with the control example. The internal structure of Examples 1 to 4 has good continuity and high temperature resistance. However, the control example showed obvious discontinuity and faults. The viscosity changes of Examples 1 to 4 after storage for 30 days were 1%, 0.5%, 2.1%, and 0.9%, respectively, while the viscosity of the control example increased by 70%. Therefore, the silver-ruthenium alloy slurry prepared by this method has more superior stability.

[0041] like Figure 1 and Figure 2 As shown, SEM and particle size distribution diagram can prove that the silver-ruthenium alloy obtained in Example 1 has uniform particle size distribution and good sphericity, which meets the narrow distribution particle size distribution characteristics; XRD data can show that the prepared silver-ruthenium alloy contains characteristic strong peaks of silver and ruthenium, which shows that silver and ruthenium have indeed formed an alloy phase; the above data show that the process of this patent can obtain a silver-ruthenium alloy with excellent crystal form and uniform particle size distribution.

[0042] Finally, it should be noted that the above is only a preferred embodiment of the present invention, and does not limit the present invention in other forms. Any person skilled in the art can use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A silver-ruthenium alloy slurry suitable for multilayer ceramic capacitors and a preparation process thereof, characterized in that: The preparation method of the slurry comprises the following steps: S1. The ruthenium target is pre-treated by sandpaper polishing to remove the oxide layer on its surface, and a treated ruthenium target is obtained after drying; the treated ruthenium target is immersed in a solution containing silver nitrate, and a nanosecond pulse laser is used to focus on the surface of the ruthenium target for laser scanning and ablation; after the ablation is completed, the ruthenium target is taken out, and the liquid after the laser scanning and ablation is collected and centrifuged, and after washing and centrifugation, it is dried to obtain a powder product, which is a silver-ruthenium alloy material. S2. The silver-ruthenium alloy material obtained in step S1 is placed in a ball mill with an organic additive, an inorganic non-metallic powder, and other metal powders in proportion and mixed evenly under high-energy graded ball mill stirring. After keeping warm for a period of time, a silver-ruthenium alloy slurry is obtained.

2. The silver-ruthenium alloy slurry suitable for multilayer ceramic capacitors and the preparation process thereof as claimed in claim 1, characterized in that: The purity of the ruthenium target in step S1 is greater than 99%.

3. The silver-ruthenium alloy slurry suitable for multilayer ceramic capacitors and the preparation process thereof as claimed in claim 1, characterized in that: The silver nitrate-containing solution in step S1 comprises 0.1 to 2.5 mol / L of silver nitrate and 0.1 to 10 g / L of a surfactant, polyvinyl pyrrolidone (PVP).

4. The silver-ruthenium alloy slurry suitable for multilayer ceramic capacitors and the preparation process thereof as claimed in claim 1, characterized in that: The parameters of the nanosecond pulse laser described in step S1 are: laser energy of 1 to 50 W, and wavelength of 266 nm to 10.6 μm.

5. The silver-ruthenium alloy paste suitable for multilayer ceramic capacitors and the preparation process thereof as claimed in claim 1, characterized in that: The laser scanning ablation described in step S1 is performed for 0.1 to 3 hours, and the particle size of the silver-ruthenium alloy material is controlled to be 10 nm to 2 μm.

6. The silver-ruthenium alloy slurry suitable for multilayer ceramic capacitors and the preparation process thereof as claimed in claim 1, characterized in that: The weight proportions of the components of the silver-ruthenium alloy slurry described in step S2 are: 50-90% of silver-ruthenium alloy material, 2-20% of organic additives, 2-15% of inorganic non-metallic powder, and 6-15% of other metal powders.

7. The silver-ruthenium alloy slurry suitable for multilayer ceramic capacitors and the preparation process thereof as claimed in claim 1, characterized in that: The organic auxiliary agent described in step S2 includes one or more of terpineol, butyl carbitol, oleic acid, stearic acid, ethyl acetoacetate, butyrylacetone, polyethylene glycol, epoxy resin, polydimethylsiloxane, ethyl cellulose, amino acid, hexadecyltrimethylammonium bromide, mercaptan, sodium dodecylbenzene sulfonate, and sodium polyacrylate.

8. The silver-ruthenium alloy paste suitable for multilayer ceramic capacitors and the preparation process thereof as claimed in claim 1, characterized in that: The inorganic non-metallic powder described in step S2 is one or more of silicon oxide, cerium oxide, carbon powder, aluminum oxide, zinc oxide, titanium carbide, and titanium diboride.

9. The silver-ruthenium alloy paste suitable for multilayer ceramic capacitors and the preparation process thereof as claimed in claim 1, characterized in that: The other metal powders described in step S2 are one or two of pure silver powder, ruthenium powder, palladium powder, copper powder or nickel powder with a particle size ranging from 20 nm to 2 μm.

10. The silver-ruthenium alloy paste suitable for multilayer ceramic capacitors and the preparation process thereof as claimed in claim 1, characterized in that: The stirring conditions of the high-energy graded ball milling described in step S2 are as follows: a ball milling speed of 500 to 2000 rpm, a ball milling time of 0.5 to 5 h, a ball graded diameter range of 0.5 to 5 cm; and a holding temperature of 20 to 90° C. after ball milling for 0.5 to 2.5 h.

Citation Information

Patent Citations

  • Metallic powders for use as electrode material in multilayer ceramic capacitors and method of manufacturing and of using same

    CN111788650A

  • Contact material

    JP1982140842A

  • Electrically conductive coating for electrode

    JP1994240183A

  • Conductive paste for MLC termination

    US5670089A